Evidence Based Physiological Adaption Of The Neonate : A Literature review - Sari Rahma Fitri (Cattleya Darmaya Fortuna, 2026)
The arrival of a newborn signifies a pivotal phase in human existence, necessitating swift adaptation from prenatal to postnatal environments. During the initial minutes and hours post-birth, substantial physiological adjustments unfold across various bodily systems, encompassing respiratory, cardiovascular, thermoregulatory, metabolic, and immune functions. These alterations are crucial for ensuring viability and fostering proper growth and development. The neonatal phase, encompassing the first 28 days of life, is broadly acknowledged as the most precarious period of infancy, characterized by elevated risks of illness and demise relative to subsequent age brackets. Worldwide, neonatal mortality constitutes nearly half of all fatalities in children under five years of age, underscoring the critical importance of enhancing neonatal healthcare. While Indonesia has experienced a progressive decrease in neonatal mortality, considerable obstacles persist in attaining national health objectives and guaranteeing uniform access to high-standard maternal and newborn care. A number of conditions continue to be major factors in neonatal deaths, such as premature birth, birth asphyxia, sepsis, infections, low blood sugar, complications affecting fetal growth, and low body temperature. Insufficient early identification and delayed treatment of these issues can result in severe health consequences or fatality. Consequently, healthcare providers, specifically midwives, nurses, and doctors, need to have a thorough understanding of neonatal physiological adjustments to deliver effective, research-supported interventions during the initial postpartum phase. This review of existing academic work intends to examine the principal physiological adjustments in newborns and to consolidate contemporary, evidence-informed approaches to initial newborn care. The focus is on the significance of prompt evaluation, suitable clinical oversight, and assistive measures designed to foster a favorable transition to life outside the womb. Enhancing newborn care methodologies by deepening the comprehension of physiological adaptation is anticipated to improve infant health results, decrease avoidable fatalities, and support the attainment of more extensive objectives related to the health of mothers and children.